Handbook of research on new product development - Golder, Peter N.; Mitra, Debanjan (Cheltenham, UK Northampton, MA Edward Elgar Publishing, 2018)
New products are the major driver of revenue growth in today's dynamic business environment. In this Handbook, the world's foremost experts on new product development bring together the latest thinking on this vitally important topic. These thought-leading authors organize knowledge into useful and insightful frameworks covering all aspects of new product development: companies, collaborators, customers, context, markets, and performance. Managers will benefit from the handbook by expanding their knowledge of new product development and researchers will learn about opportunities to continue ex.
Front Matter; Copyright; Contents; List of editors and contributors; Acknowledgements. -- PART I INTRODUCTION AND OVERVIEW; 1 New product development research: consolidating the present and guiding the future. -- PART II IDEA GENERATION; 2 Taming the creative spark: insights from research on creativity in new product development; 3 The what, who and how of innovation generation; 4 Customer-driven innovation: a conceptual typology, review of theoretical perspectives, and future research directions; 5 The paradigm shift from producer to consumer innovation: implications for consumer research. 6 Institutionalizing an innovation function: moving beyond the champion. -- PART III MARKET ANALYSIS; 7 Digital multisided platforms: an innovation research agenda; 8 Innovation in China and India. -- PART IV PRODUCT DESIGN AND DEVELOPMENT; 9 The state of new product design and forecasting research: recent developments and future directions; 10 Strategic use of product enhancements: upgrades, add-ons, extras, and accessories; 11 Sustainable new product development; 12 Open Innovation in the brand management context. -- PART V COMMERCIALIZATION. 13 Global product launch: a perspective on past, present, and future research. -- PART VI MARKET OUTCOMES; 14 A summary and review of new product diffusion models and key findings; 15 Word-of-mouth processes in marketing new products: recent research and future opportunities; 16 Firm innovation and the stock market; 17 A review of crowdfunding research and findings; 18 Antecedents, consequences, and the mediating role of innovation: empirical generalizations; 19 Best practices and success drivers in new product development; Index
Includes bibliographical references and index.
Keywords: New products; Product design